Efeitos do diclofenaco sobre marcadores inflamatórios e de estresse oxidativo em ratos submetidos a consecutivos sets exaustivos - Steckling, Flávia Mariel (2021)
Physical exercise sessions represent some stress due to the fact that it alters body homeostasis. High oxygen consumption during exercise increases the production of reactive oxygen species (ROS) and pro-inflammatory proteins, resulting in oxidative stress and transient acute inflammation. Currently, non-steroidal anti-inflammatory drugs (NSAIDs), including diclofenac, have been widely used in athletic competition. Considering that athletes participate in consecutive competitions of high intensity and short duration and that these can lead to a sensation of pain and an inflammatory process, many competitors use NSAIDs as ergogenic resources or even to avoid performance losses during their competitions.However, little is known about the effects of using diclofenac on tissues during consecutive exhaustive swimming sets. Taking into account the sport specificity, most studies refer to the association of physical exercise and skeletal muscle, although, adaptive responses to physical exercise are not restricted to muscle tissue. Considering the important role of the liver during exercise, an objective of this thesis was to analyze the effects of diclofenac on liver markers, and in a second moment on muscle markers, oxidative stress, tissue damage and inflammation in sedentary rats submitted to consecutive sets of forced swimming. In the article, we highlight the role of diclofenac in modulating oxidative stress responses and inflammation and adaptation caused by high-intensity exercise in the liver. The experimental protocol was carried out with 4 distinct groups: sedentary-saline, sedentary-diclofenac, exhaustion-saline and exhaustion-diclofenac. The exercise groups were submitted to 3 consecutive sets of swimming, 48 hours apart, and the treated groups were pre-treated with diclofenac (10 mg/kg) throughout the protocol. We identified significant changes in the levels of TBARS and the GSH/GSSG ratio and an increase in the levels inflammatory markers TLR4, MyD88, IL-1β, IL-6, TNF-α and INF-γ after exhaustive exercise. All these changes were reversed by treatment with diclofenac. In the manuscript, we highlight the modulatory role of diclofenac on damage responses, oxidative stress, inflammation generated by exercise in skeletal muscle. The protocol consisted of the same 3 consecutive swimming sets, 48 hours apart, in rats treated with saline or diclofenac (10 mg/kg) (groups: sedentary-saline, saline-exhaustion, sedentary-diclofenac, and diclofenac-exhaustion). After exercise, an increase in the levels of TBARS, DCFH-DA and a decrease in the GSH/GSSG ratio, and increases in the levels of markers COX-2, TLR4, MyD88, NFκB, IL-1β, IL-6, TNF were identified -α and INF-γ and increased iNOS gene expression. These responses generated by exhaustive exercise were attenuated by treatment with diclofenac. The data obtained allow us to conclude that diclofenac interferes with oxidative/inflammatory markers in adaptive responses generated by physical exercise in muscle and liver tissue, postponing fatigue and, in parallel, changing the mechanisms which are necessary for tissue adaptation to physical exercise of swimming.